Children and adolescents with overweight or obesity exhibit poor cardiorespiratory performance and elevated energy expenditure during an exercise task - Carlos Sepúlveda; Matías Monsalves-Álvarez; Rodrigo Troncoso; Gerardo Weisstaub (PLoS ONE, 2025)
Background Cardiorespiratory fitness (CRF) is essential for cardiovascular and metabolic health at any age. High levels of CRF are linked to better performance in sports and daily activities among children and adolescents. Conversely, being overweight or obese is associated with lower CRF, which can lead to decreased daily energy expenditure and reduced physical activity. This study aims to investigate CRF performance and energy expenditure in response to an exercise task among children and adolescents. Methods The sample consisted of 242 children and adolescents aged 8–16 years, categorized by healthy weight, overweight, obesity, and levels of cardiorespiratory fitness (low or high). Assessments included nutritional status (body mass index as Z-score), blood pressure (measured in mmHg), and electrocardiograms. Maximal oxygen consumption and ventilatory thresholds were measured using a modified Balke protocol. After initial screening, all participants performed an exercise task that involved stepping up and down on a 2-step footstool at a rate of 30 steps per minute (60 bpm) for 3 minutes. Results Significant differences were observed in maximal oxygen consumption values between boys and girls across different weight categories: healthy weight (♀ 35.0 ± 5.9 ml·kg -1 ·min -1 ; ♂ 38.8 ± 6.1 ml·kg -1 ·min -1 ), overweight (♀ 32.7 ± 5.2 ml·kg -1 ·min -1 ; ♂ 35.9 ± 5.3 ml·kg -1 ·min -1 ), and obesity (♀ 27.6 ± 6.3 ml·kg -1 ·min -1 ; ♂ 32.8 ± 5.8 ml·kg -1 ·min -1 ) (p < 0.05). Both overweight and obese boys and girls showed a higher percentage of maximal oxygen consumption at ventilatory threshold 1, along with increased heart rate, perceived exertion, and percentage of maximal oxygen consumption during the exercise task. Their recovery was less efficient, as indicated by the Ruffier and Dickson indices. Additionally, low CRF was associated with higher oxygen consumption at both ventilatory thresholds, elevated heart rate, and poorer scores on the Ruffier and Dickson indices. Regarding energy expenditure during the exercise task, overweight and obese participants exhibited a higher energy cost rate and perceived exertion compared to those of healthy weight. Conclusions Our findings indicate that both overweight and obese girls and boys have lower levels of CRF. These children also engaged in exercise at a higher intensity and expended more energy, with longer recovery times for their heart rates. Furthermore, our results suggest that low CRF levels are linked to these factors.